Lernwelt Makerspace Perspektiven im öffentlichen und wissenschaftlichen Kontext - Heinzel, Viktoria; Seidl, Tobias 1981-; Stang, Richard 1959- (De Gruyter Saur, 2020)
First developed in Anglo-American contexts, a makerspace is a new kind of teaching and learning space. Already popular outside institutions, colleges and libraries are now also developing concepts for makerspace design. This volume is the first systematic study of these developments, exploring concepts such as how the learning environment can be structured as a makerspace
Keywords: Makerspace; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / School Media; Lernort; FabLab; Lernumwelt; Aufsatzsammlung